Stories of Women Gender and Narrative in the Postcolonial Nation - Boehmer, Elleke (Manchester University Press, 2009)
Elleke Boehmer's work on the crucial intersections between independence, nationalism and gender has already proved canonical in the field. 'Stories of women' combines her keynote essays on the mother figure and the postcolonial nation, with incisive new work on male autobiography, 'daughter' writers, the colonial body, the trauma of the post-colony, and the nation in a transnational context. Focusing on Africa as well as South Asia, and sexuality as well as gender, Boehmer offers fine close readings of writers ranging from Achebe, Okri and Mandela to Arundhati Roy and Yvonne Vera, shaping these into a critical engagement with theorists of the nation like Fredric Jameson and Partha Chatterjee.This new paperback edition will be of interest to readers and researchers of postcolonial, international and women's writing; of nation theory, colonial history and historiography; of Indian, African, migrant and diasporic literatures, and is likely to prove a landmark study in the field.